Waste biomass valorisation of Bambusa vulgaris dust and Delonix regia pods: Characterization and kinetic study - Tiwari A.K.; Prasad N.; Jana S.K.; Srivastava N.; Alshahrani M.Y.; Ahmad I.; Mishra P.K.; Pal D.B. (My University, 2025)
The present study is focused to biomass-based exploration via physiochemical characterization of biomass waste Bambusa vulgaris dust (BD) and Delonix regia pods peels (DRP) for the enhancement of biofuels production using suitable methods. Physiochemical characteristics of the selected biomass wastes were determined using proximate and ultimate analysis, FTIR spectroscopy, elemental analysis, TGA (thermo-gravimetric analysis), and XRD (X-ray diffraction). Ultimate analysis result of BD showed good amount of lignin (18–27 %) and cellulose (48–72 %) present in it. Both BD and DRP biomasses showed the higher calorific value of ∼16 MJ/kg. Model free methods like Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) were applied for the determination of kinetic parameters. The calculated average activation energy was 85.19 and 143.96 kJ/mol using KAS model and 84.82 and 143.32 kJ/mol using FWO model for BD and DRP biomass, respectively. © 2022 Elsevier Ltd